Doping in cyclism: results of unannounced controls in Flanders (1987-1994) - Delbeke, F. T. (International Journal of Sports Medicine, 1996)
Unannounced doping control in cyclism, the most favourite sport in Flanders, resulted in 7.8% positive cases in 4374 analysed samples during the period 1987-1994. Ephedrines, amphetamine and nandrolone were frequently misused and polydrug abuse including ephedrines and amphetamine seemed to be very popular. The abuse of methamphetamine, methylphenidate and pemoline, formerly favourite drugs in cyclists is decreasing while prolintane, codeine and the anabolic steroids nandrolone and testosterone were more frequently detected. The misuse of forbidden substances by athletes competing in the official Belgian Cyclist Federation and in amateur federations was 5.8% and 8.9%, respectively. Several cyclists however attempted to circumvent doping control.